Wawacan Layang Syekh Abdul Qodir Jaelani dan Manaqib Jawahirul Ma'ani:: Kajian Filologis-Komparatif Pesantren - Muhammad Jazuli; Panji NurMuhammadSholih; Muhammad Zaironi (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
This study compares two hagiographic texts about Syekh Abdul Qadir al-Jailani, founder of the Qadiriyyah order: the Wawacan Layang Syekh Abdul Qodir Jaelani, a 1939 Sundanese literary poem, and the Manaqib Jawahirul Ma'ani, a manaqib text by KH. Ahmad Jauhari Umar (Pondok Pesantren Darussalam, Tegalrejo, Pasuruan) still practiced in Nahdlatul Ulama pesantren networks. It describes both texts philologically, compares their narrative structures, and examines why the Manaqib remains actively used while the Wawacan does not. Using qualitative comparative philology, textual data were analyzed through content and narrative analysis, triangulated with semi-structured interviews with twelve informants (two kiai who grant ijazah, ten santri/jamaah practitioners), framed by philological theory, hagiography-genre theory, and Alatas's (2021) concept of religious authority as articulatory labor. Findings show both texts narrate overlapping episodes of Syekh Abdul Qadir's life but diverge sharply in function: the Wawacan remains a literary-aesthetic artifact, while the Manaqib operates as a ritual instrument bound by an ijazah-sanad system restricting unauthorized reproduction. Practitioners themselves consistently draw this boundary, treating wawacan-type narratives as folklore versus the manaqib's status as a sanad-bound devotional text. This asymmetry shows hagiographic texts become instruments of religious authority only through sustained institutional labor — textual survival in pesantren depends less on literary merit than on active mechanisms of transmission and authority-building.